Reactivity of human Lyme borreliosis sera with a 39-kilodalton antigen specific to Borrelia burgdorferi. - Simpson, W J (1990)
Borrelia burgdorferi is the causative agent of Lyme borreliosis, a spirochetal illness with a variety of acute clinical manifestations that may lead to debilitating neurological and arthritic complications. Diagnosis is difficult because symptoms mimic a variety of unrelated clinical conditions, spirochetes cannot always be isolated from infected patients, and current serological tests are frequently inconclusive because of the presence of cross-reacting non-B. burgdorferi antibodies. To identify antigens specific to B. burgdorferi that could be used in the serodiagnosis of Lyme borreliosis, we screened a Borrelia DNA expression library in Escherichia coli for antigens reactive with human Lyme borreliosis sera. One clone carried a 6.3-kilobase EcoRI chromosomal fragment (pSPR33), which encoded two species-specific antigens with molecular masses of 28 (P28) and 39 (P39) kilodaltons (kDa). These two antigens were immunologically distinct from OspA, OspB, and the 41-kDa flagellin. Ninety-four serum specimens from patients having Lyme borreliosis were tested for reactivity with P39. All of 33 the serum specimens with immunofluorescence assay titers of greater than or equal to 1:256, 13 of 17 serum specimens with titers of 1:128, and 14 of 44 serum specimens with titers of less than or equal to 1:64 reacted with P39. Notably, many sera reactive to P39 did not appear to react with the 41-kDa flagellin. Therefore, antibody to P39 could be mistaken for antibody to the 41-kDa flagellin in tests of human sera by Western blot (immunoblot). Twenty-five control serum specimens, which included sera from syphilitic, relapsing fever, and amyotrophic lateral sclerosis patients as well as from 10 normal individuals, did not react to P39. Our data suggest that P39 may be a useful antigen for the serological confirmation of Lyme borreliosis.